Gamification of Information System Testing-Design Consideration through focus group discussion - Memar, Navid; Krishna, Aneesh; McMeekin, David; Tan, Tele (2017)
This paper presents the design consideration of gamifying Information System Testing through results obtained from various focus group sessions with software developers and testers. The intention is to provide new testing strategies and tools that can help Information System testing to be more efficient while providing an engaging and rewarding test environment for the tester. Gamification may be a solution to raise testers’ engagement in, as it can potentially remedy the high degree of repetition and ensuing boredom for a tester in the testing phase. Findings, suggest that gamification may be an element to advance the testing efficiency. Moreover, system and task knowledge, the objectives of the actual system, time constraints and required tools for performing testing task are essential to have an efficient testing performance. Participants stated that points, levels, meaningful gifts, progressions, provision of choice and feedback are the main elements a gamified testing platform should have.